Modeling the management process in the function of long-term goal fulfillment in Croatian companies : Modeliranje procesa upravljanja u funkciji dugoročnog ispunjavanja ciljeva u hrvatskim poduzećima - Šupuković, Vedran (Array, 2019)
The issue of management process in all organizations with a pronounced hierarchical structure is extremely complex and equally abstract to both the participants themselves and all those who deal with the study of this topic. The management process involves decision-making based on appropriate economic analysis, experience, practice, micro and macro environment, and the ability of an individual manager to create a symbiosis based on all the knowledge that will ultimately lead to making an appropriate business decision. The aim of this paper is to build a presentation of the model, which in this case will improve the economic community and enrich the everyday work of companies. This will allow the ownership and management structures of a large number of inadequately structured and internally non-institutionalized companies to become active and passive managers of all business relations within the companies in which they operate, instead of active or passive observers. In this paper, a management model will be presented based on the data researched within five variables: quality of human resources, economic incentives, development perspectives, managerial capabilities of subordinates and business satisfaction. One of the aims of this paper is precisely to explore how these variables influence the business satisfaction of Croatian companies. The research was conducted in the territory of the Republic of Croatia, in all regions, on a representative sample, while representatives of the companies were surveyed. The answers obtained were analysed descriptively, through the regression model. It has been proven that the greatest influence on pleasure in business is influenced by managerial capacities, where beta coefficients is 0.367. Slightly less impact on the pleasure of doing business has the development of enterprises and incentives from the budget, while the smallest impact on the pleasure of doing business has human potential.